Near infrared analysis for nutritive attributes of tedera (Bituminaria bituminosa var. albomarginata). Issue 3 (June 2017) - Adriansz, TD; Hardy, JLM; Milton, JTB; Oldham, CM; Real, D
Tedera ( Bituminaria bituminosa var. albomarginata ) is a perennial legume native to Lanzarote, an island within the Canary Islands; known for its dry environment. It is a plant known as a grazing option within that island. Tedera was tested for its potential as an optional feed source for sheep grazing under Western Australian conditions, also known for its frequent periods of drought stress. Four sets each of 35 seasonal samples were taken from seven accessions of the legume, in an area known to have less than 600 mm of rain each year. Milled leaf – stem samples were analysed for a series of nutritive attributes and calibrations were developed using information in near infrared spectra. This paper presents findings, which demonstrate that some sound calibrations are possible for major nutritive attributes including acid detergent fibre, crude protein, calcium and chloride; for these attributes the ratio of performance to deviation exceeded a value of 4.5.